Transcriptomic identification of potential antioxidative enzyme regulators of the gametophytic-to-embryogenic switch in barley microspores - Nowicka, Anna; Milec, Zbyněk; Krzewska, Monika; Kopeć, Przemysław; Springer, Agnieszka; Dubas, Ewa; Żur, Iwona (Frontiers in Plant Science, 2026)
Microspore embryogenesis (ME) relies on the cellular reprogramming of the default gametophytic developmental pathway, which normally directs microspores toward pollen formation, into an embryogenic pathway that leads to the development of embryo–like structures (ELS) and, subsequently, haploid or doubled haploid (DH) plants. To test how redox control underpins this switch, we have carried out an extended in silico analysis of previously published RNA-seq data from two barley cultivars differing in ME competence (Igri, responsive; Golden Promise, recalcitrant) across four early induction stages (0–III). A curated set of 472 antioxidant/redox genes—core detoxification enzymes, the ASC–GSH cycle, TRX/GRX/PRX systems and GSTs—was examined. The analysis revealed that the expression of antioxidative defense genes is dynamically modulated during ME induction, underscoring the importance of redox homeostasis in successful microspore reprogramming. Both cultivars shared a late (stages II–III) program with increased SODs, selected CAT/GPX genes, rising MDHARs, deployment of specific TRX/GRX/PRX members and broad GSTs upregulation. Divergence emerged during progression: Igri showed a pronounced stage-III rise of GRs and targeted TRX/GRX/PRX transcripts, together with stronger activation of multiple GSTs. When considered alongside diverse experimental data, these stage-restricted, cultivar-biased signatures support a hypothetical model in which strengthened ASC–GSH recycling and thiol-redox hubs sustain H2O2 signaling while limiting oxidative damage. Targeting MDHARs, GRs, selected TRX/GRX/PRX genes, and GST subsets could improve ME efficiency and accelerate the integration of DH technology into modern crop breeding programs.